Study of bovine serum albumin interaction with zinc oxide surfaces by force field simulations. Issue 1 (January 2021) - Hematian, H; Rezek, B
Abstract: We studied the interactions of bovine serum albumin (BSA) molecule with ZnO surfaces by force field simulations. The different orientations of BSA over the two main nonpolar wurtzite ZnO surfaces (10 1 ¯ 0) and (11 1 ¯ 0) have been investigated. These surfaces contain both Zn and O atoms. We compare the results also with polar Zn-face (0001) surface. The results demonstrate tendency of BSA molecule for being adsorbed on the ZnO surface in specific orientations. This happens either by bonding between a hydrogen atom of BSA molecule to an oxygen atom of the ZnO surface or by physical attraction inducing ZnO atoms displacement in some cases.